Assessment of Process Variables on Vitamin B12 Production in Fermented Dairy Product Including Propionic Acid - Massoud, Ramona; Khosravi-Darani, Kianoush; Golshahi, Milad; Sohrabvandi, Sara; Mortazavian, Amir M. (Current Nutrition & Food Science, 2020)
The fermented dairy products produced by various microorganism’s activity provide valuable nutrients for human. Fermentation affects the physicochemical and organoleptic characteristics of foods as well as human health. In the present review, we describe the production of vitamin B12 in a fermented dairy product by Propionibacterium species. The effect of the process variables on vitamin B12 production in fermented dairy products e.g. pH, temperature, different carbon and nitrogen sources as well as the type and size of inoculum, the fermentation time and fermentation strategy, etc. are discussed. Finally, fermentation strategy, inoculum preparation of Propionibacterium freudenreichii subsp. Shermanii, methods of determining biomass and Vitamin B12 concentration are reviewed and their effects on vitamin B12 production are mentioned. Propionibacteria are so popular due to their unique characteristics such as being safe, convenient and economical. Among all the highest efficiency was observed by P. freudenreichii. To achieve this purpose, some appropriate situations need to be considered. The best carbon source for this bacterium to produce biomass is lactate, the suitable pH for growth of the Propionibacterium species is in the range of 6 to 7 and the fed-batch is most preferable for vitamin B12 production.
Keywords: vitamin B12